World AIDS Day Report 2022 - UNAIDS (United Nations, 2022)
The World AIDS Day (WAD) report is one of two annual UNAIDS flagship reports. The report is planned to be launched on 29 November 2022, ahead of 1 December, the international day dedicated to raising awareness of the HIV epidemic and remembering those who have died of AIDS-related causes. The WAD Report for 2022 will build upon the 2022 World AIDS Day theme “Equalize” by sharing new analyses of UNAIDS data that underscore where the inequality gaps are, why they are so crucial, and the practical steps that can be taken to close those gaps.